Atividade mutagênica de plantas medicinais - Varanda, Eliana Aparecida [UNESP] (My University, 2006)
The number of studies of genotoxic activity of medicinal plants has been growing alongside with their increasing therapeutic use and scientific interest in proving their effectiveness for a variety of pharmacological purposes. This reflects the fact that many of the plants used by great numbers of people, in spite of their proven pharmacological value, can also cause harmful changes in the DNA. The risks are greater when alternative treatments are applied in an uncontrolled way, without due attention to correct botanical identification, to the part of the plant that should to be used and to the method of preparation and administration. In this review, aspects of the mutagenic activity of some medicinal plants are discussed.

Os estudos de genotoxicidade com plantas têm crescido juntamente com o aumento do uso terapêutico e com o interesse de comprovação da eficácia das mesmas nas mais diversas finalidades farmacológicas. Isso deve-se ao fato de muitas das plantas utilizadas por um grande número de pessoas, apesar de possuírem propriedades farmacológicas, também podem causar alterações no DNA. Os riscos são ainda maiores quando o uso de tratamentos clínicos alternativos dá-se de forma não controlada, sem a devida atenção quanto a identificação correta da planta, a parte do vegetal a ser utilizada e a forma de preparo e administração. Nessa revisão são abordados aspectos da atividade mutagênica de algumas plantas medicinais.
Mutagenic activity of medicinal plants
Keywords: Genic mutations; Genotoxicity; Medicinal plants; DNA; plant extract; alternative medicine; drug efficacy; gene mutation; genotoxicity; human; medicinal plant; mutagenic activity; nonhuman; risk factor; side effect